The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/healthcare11070932
|View full text |Cite
|
Sign up to set email alerts
|

Mortality and Survival Factors in Patients with Moderate and Severe Pneumonia Due to COVID-19

Abstract: During the pandemic, some mortality-related factors were age, sex, comorbidities (obesity, diabetes mellitus, and hypertension), recovery time, hospitalizations, and biochemical markers. The present work aimed to identify the mortality and survival factors in adults with moderate and severe pneumonia due to COVID-19 during the first and second waves of the pandemic in Mexico at a third-level hospital (High-Specialty Regional Hospital of Ixtapaluca (HRAEI), Ixtapaluca, Estado de Mexico, Mexico). A database was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
(52 reference statements)
0
2
0
Order By: Relevance
“…In this context, O3FAs offer a nutritionally based option for their potential mechanisms underlying multiple actions. In this sense, previous studies in Mexico have indicated the leading risk factors for mortality in middle-aged COVID-19 patients: male, hypertension, drug addiction, and alcoholism [9,51,52]. However, scarce data support the beneficial effects of specific drugs or supplements in Mexican COVID-19 patients, triggering misconduct in drug availability, marketing, and application [53].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, O3FAs offer a nutritionally based option for their potential mechanisms underlying multiple actions. In this sense, previous studies in Mexico have indicated the leading risk factors for mortality in middle-aged COVID-19 patients: male, hypertension, drug addiction, and alcoholism [9,51,52]. However, scarce data support the beneficial effects of specific drugs or supplements in Mexican COVID-19 patients, triggering misconduct in drug availability, marketing, and application [53].…”
Section: Discussionmentioning
confidence: 99%
“…Severe infections are related to comorbidities, such as obesity, diabetes, chronic obstructive pulmonary disease, chronic heart failure, coronary artery diseases, metabolic syndrome, and hypertension [8]. In this regard, Galindo-Oseguera et al identified an increased risk of mortality in the presence of hypertension and diabetes linked to an exacerbated inflammatory profile in moderate and severe pneumonia due to COVID-19 in patients attending the High Specialty Regional Hospital of Ixtapaluca, Mexico (HRAEI), a regional hospital [9]. SARS-CoV-2 infection causes a pattern of metabolic and clinical manifestations, leading to leukocytopenia, lymphopenia, and elevated levels of C-reactive protein (CPR) in patients with the primary form of COVID-19 [1, [10][11][12].…”
Section: Introductionmentioning
confidence: 99%